Does a vascular supercharge improve the clinical outcome for free jejunal transfer?. Issue 3 (15th November 2012) - Numajiri, Toshiaki; Sowa, Yoshihiro; Nishino, Kenichi; Fujiwara, Hitoshi; Nakano, Hiroshi; Shimada, Taketoshi; Hisa, Yasuo
Abstract: To clarify whether a supercharged free jejunal transfer would have a different clinical outcome from the usual transfer method, we examined clinical data from cases of esophago‐pharyngeal reconstruction. Fifty‐three patients in whom the hypopharynx and cervical esophagus was reconstructed with a free jejunal transfer were divided into two groups: 19 normal procedures and 34 supercharged. Clinical outcomes including intraoperative and postoperative events, complications and deglutition were compared statistically. There were no significant differences between the groups in terms of the rates of free flap failure, leakage, stenosis, drinking status, dysphagia, or operating time. There were no significant advantages in clinical outcomes when using a supercharge. However, supercharged flaps with an intraoperative arterial thrombosis were all rescued and survived. Thus, a supercharge in free flap is not necessary for all cases. Its indication should be limited to cases when free flaps are not reliable because of intraoperative thrombosis and arterial insufficiency. © 2012 Wiley Periodicals, Inc. Microsurgery, 2013.